The moderating role of technology awareness in the behavioural intention - Hafizah Mohamad Hsbollah, Haslinda Hassan, Raja Haslinda Raja Mohd Ali, (Opción, 2019)
This study aims to examine the moderating role of technology awareness in the students’ behavioural intention to use accounting software. The model of this study was developed based on the technology acceptance model (TAM) and the theory of planned behaviour (TPB). Data were gathered via survey questionnaires established using instruments from prior studies to adequately reflect the underlying theoretical factors identified. We present the initial finding of the pilot study from the surveys distributed to 32 accounting students at Universiti Utara Malaysia. The results showed that the Cronbach alpha coefficient values suggested that all constructs had good internal consistency.